ADDITION AND IDENTITY CRISIS IN ADOLESCENT CHILDREN - Karpuszenko, Elena (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка. Фізичне виховання, спорт і здоров’я людини, 2014)
The frequently raised question in contemporary world is what the future generation of young people will be like, how their identity is formed and what is important to them. The attention is also being paid to numerous threats that affect a person in current reality and a number of risky behaviour these people are involved in. This study attempts to answer whether addiction to psychoactive drugs might result from unsolved developmental crises and which factors can stimulate young people to start taking psychoactive drugs, especially narcotics and make them addicted to these substances.